Does the thickness of the resin cement affect the bond strength of a fiber post to the root dentin? - Perez, Bianca E. M. [UNESP]; Barbosa, Silvia H. [UNESP]; Melo, Renata M. [UNESP]; Zamboni, Sandra C. [UNESP]; Özcan, Mutlu; Valandro, Luiz Felipe; Bottino, Marco A. [UNESP] (My University, 2006)
This study aimed to evaluate the influence of cement thickness on the bond strength of a fiber-reinforced composite (FRC) post system to the root dentin. Eighteen single-rooted human teeth were decoronated (length: 16 mm), the canals were prepared, and the specimens were randomly allocated to 2 groups (n = 9): group 1 (low cement thickness), in which size 3 FRC posts were cemented using adhesive plus resin cement; and group 2 (high cement thickness), in which size 1 FRC posts were cemented as in group 1. Specimens were sectioned, producing 5 samples (thickness: 1.5 mm). For cement thickness evaluation, photographs of the samples were taken using an optical microscope, and the images were analyzed. Each sample was tested in push-out, and data were statistically analyzed. Bond strengths of groups 1 and 2 did not show significant differences (P = .558), but the cement thicknesses for these groups were significantly different (P < .0001). The increase in cement thickness did not significantly affect the bond strength (r2 = 0.1389, P = .936). Increased cement thickness surrounding the FRC post did not impair the bond strength.
Keywords: All Bond 2; dentin bonding agent; Duo Link; phosphoric acid; resin cement; silane derivative; clinical trial; controlled study; dental acid etching; dental bonding; dental surgery; endodontics; materials testing; mechanical stress; randomized controlled trial; surface property; tooth crown; tooth pulp; ultrastructure; Dentin-Bonding Agents